A IMPLEMENTATION OF INCLUSIVE EDUCATION IN PRIMARY SCHOOLS: A LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Muslimah, Revi; Darmayanti, Mela (JPI (Jurnal Pendidikan Inklusi), 2024)
Inclusive education has become the main focus in supporting successful learning for all students, especially those with special needs. This research aims to investigate the implementation of inclusive education in elementary schools. This research uses literature review and bibliometric methods with the help of the publish or perish application and Google Scholar with the keywords "inclusive education" and "primary school." the search was carried out by looking for 100 relevant articles and saved via Vosviewer to get data. Through analysis of various literature sources, this research identified main problems, such as lack of teacher training and lack of infrastructure support. Literature findings also highlight that a collaborative approach between teachers, parents, and educational experts is essential. The conclusion of this literature review emphasizes the need for integration strategy policies and implementing inclusive practices to ensure the successful implementation of inclusive education in elementary schools and provide training to teachers to implement inclusive education optimally.